A criminologia crítica e o direito penal mínimo: avanços e retrocessos - Silva, Flavia Augusta Bueno da [UNESP]; Rocha, Luiz Carlos da [UNESP] (My University, 2012)
This paper presents the emergence of knowledge-criminals criminal character of oppositional discourses to biologists and to the ideals of social defense, denouncing the criminal policies of discriminatory bias that still permeate the administrative practices of conflict. To this end, we examine the precepts of Critical Criminology revolutionary scenario that emerged in the 60s. His propositions denounced emphatically that social control was exercised by class interests and that the criminal policies were a reflection of capitalist domination extended to the criminal area. Accordingly, the present knowledge of such criminology, whose critical analysis culminated in the drafting of an alternative program for the management of the crisis of contemporary legalcriminal: the minimum criminal law and its proposed alternative sentences.

Este trabalho visa apresentar a emergência dos saberes criminopenais de caráter contestador aos discursos biologistas e aos ideais de defesa social, que denunciam o viés discriminatório das políticas criminais que ainda hoje permeiam as práticas administrativas de conflito. Para tanto, examinamos os preceitos da Criminologia Crítica que emergiu no cenário revolucionário dos anos 60. Suas proposições denunciavam enfaticamente que o controle social era exercido por interesses de classe e que as políticas criminais eram um reflexo dessa dominação capitalista estendida à área criminal. Nesse sentido, apresentamos os saberes de tal criminologia, cujas análises críticas culminaram na elaboração de um programa alternativo para a administração da crise jurídico-penal da contemporaneidade: o direito penal mínimo e sua proposta de penas alternativas.
The critical criminology and criminal law minimum: advances and setbacks
Keywords: Critical criminology; Minimum criminal law; Sentencing alternatives; Criminologia crítica; Direito penal mínimo; Penas alternativas